Activation of TLR‐4 to produce tumour necrosis factor‐α in neuropathic pain caused by paclitaxel. (12th November 2014) - Wu, Z.; Wang, S.; Wu, I.; Mata, M.; Fink, D.J.
Abstract Background Neuropathic pain is a common complication of treatment with the anti‐neoplastic drug paclitaxel. Animal studies suggest neuroinflammation and transient receptor potential channels TRPA1 and TRPV4 are involved in the pathogenesis of pain in this condition. However, how neuroinflammation and TRPA1 and TRPV4 are linked to cause pain in paclitaxel‐treated animals is not known. Methods Paclitaxel‐induced pain was modelled by IP injection of paclitaxel (16 mg/kg) once a week for 5 weeks. The role of toll‐like receptor 4 (TLR‐4) in tumour necrosis factor‐α (TNF‐α) production and the effect of TNF‐α on the expression of TRPA1 and TRPV4 were evaluated in vitro and in vivo. TNF‐α signalling in dorsal root ganglion (DRG) was blocked by expressing soluble TNF receptor I (TNFsR) from a herpes simplex virus (HSV)‐based vector (vTNFsR). Results Paclitaxel treatment increased the expression and release of TNF‐α in satellite glial cells and increased the expression of TRPA1 and TRPV4 in DRG neurons in animals. In vitro, paclitaxel enhanced the expression and release of TNF‐α in enriched primary satellite glial cells, an effect that was blocked by an inhibitor of TLR‐4. Direct application of TNF‐α to primary DRG neurons in culture up‐regulated the expression of TRPA1 and TRPV4. In vivo, vector‐mediated TNFsR release from DRG neurons reduced paclitaxel‐induced up‐regulation of TRPA1 and TRPV4 expression and prevented paclitaxel‐induced pain. Conclusion These results suggest that paclitaxel activation of TLR‐4 to cause release of TNF‐α from satellite glial cells increases the expression of TRPA1 and TRPV4 in DRG neurons to cause neuropathic pain.